Beberapa Aspek Reproduksi Siput Lambis lambis di Pesisir Perairan Yenusi, Biak - Andriani Widyastuti; Ludi Parwadani Aji (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Some Aspects of Reproduction in Conch Lambis lambis of Yenusi Coastal Waters, Biak. Lambis lambis is a very popular conch species that has been harvested in all sizes encountered. This condition is very alarming because in the long term, its existence in nature will be reduced because there is no chance to reproduce naturally. This study aims to determine the sex ratio and gonad maturity levels of L. lambis in Yenusi waters, so the appropriate time of harvest can be arranged. Samples were collected every month from January to December 2013. Testing and histological analysis were performed in the laboratory. Samples collected were 99 individus with the number of males 45 individus and females 54 individus. The sex ratio of males and females was 1.0:1.2. Gonad maturity level found included all four stages of gonadal development, from TKG I to TKG IV. Gonadal development showed the process of formation and maturation, and the spawning occured throughout the year, with peak spawning in January until March 2013. The size of the shell length obtained ranged from 4.55 to 13.72 cm indicating over-exploitation. Due to the custom local where residents harvested the conches in all sizes found, sustainable management strategies are urgently needed, including moratorium period when L. lambis is at the peak of spawning, and harvest should only be performed on adult individuals with a minimum shell size of 7 cm, while observing the thickness of the shell and marginal digitations have been formed.